DESTRESS - soft stimulation treatments of geothermal reservoirs, Iceland - Dahm, Torsten; Zimmermann, Günter; Hofmann, Hannes; Huenges, Ernst; Heimann, Sebastian; Milkereit, Claus; Hjörleifsdóttir, Vala; Ásgeirsdóttir, Ragnheidur St.; Magnússon, Rögnvaldur; Flovenz, Ólafur; Grigoli, Francesco; Wiemer, Stefan (GFZ Data Services, 2020)
Abstract Near Reykjavik/Iceland, a "soft stimulation” geothermal experiment was performed in the frame of the DESTRESS project in 2019. The installed seismic stations consist of short period, and borehole stations in and around Geldinganes, NE of Reykjavik. The task of this network is the monitoring of the seismic events in the area around the stimulation site. The installation started in late 2018 with 6 short period stations (Reykjavik Energy). Since July 2019 additional seismic stations were integrated as a small scale array on the island Geldinganes and additional short period stations. A borehole geophone chain was installed with 17 short period 3-component geophones with a vertical spacing of 10 meter in the depth interval 1040m to 1200 m. Waveform data are available from the GEOFON data centre, under network code YG.